2007
DOI: 10.1590/s0124-00642007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Contaminación de los Parques Públicos de la Localidad de Suba, Bogotá con Nemátodos Zoonóticos

Abstract: The high percentage of recreational areas so polluted indicated that these places would constitute a risk factor for the transmission of parasitic diseases to animals and human beings. Due to this sanitary problem's relevance in public health programmes, government policy must be determined involving communities so that people are educated to improve their sanitary practices in recreational places regarding caring for their pets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
0
1
7
Order By: Relevance
“…With regards to soil samples with eggs and larvae of Ancylostoma spp., the frequency in this study (46.8%) was higher than the cities of some countries, such as Bogotá, Colombia (10.7%) 31 , Kaduna, Nigeria (9%) 22 , Wrocław, Poland (4.9%) 30 , Madrid, Spain (3%) 10 and different regions of Costa Rica (2%) 29 . Concerning the Brazilian cities, our results with hookworms in Guarulhos were similar to the recorded in Araçatuba (São Paulo State) by NUNES et al (2000) 28 , who found 46% of the sand samples contaminated with Ancylostoma spp.…”
Section: Discussioncontrasting
confidence: 48%
“…With regards to soil samples with eggs and larvae of Ancylostoma spp., the frequency in this study (46.8%) was higher than the cities of some countries, such as Bogotá, Colombia (10.7%) 31 , Kaduna, Nigeria (9%) 22 , Wrocław, Poland (4.9%) 30 , Madrid, Spain (3%) 10 and different regions of Costa Rica (2%) 29 . Concerning the Brazilian cities, our results with hookworms in Guarulhos were similar to the recorded in Araçatuba (São Paulo State) by NUNES et al (2000) 28 , who found 46% of the sand samples contaminated with Ancylostoma spp.…”
Section: Discussioncontrasting
confidence: 48%
“…Se encontró 1.4 % de Dipylidium caninum, resultado similar al obtenido por Terán (Polo-Terán et al, 2007), debajo pero diferente al 11,76 % obtenido de Villagómez Garzón (Villagómez Garzón, 2018) y al 25.18 % obtenido por Diana (Tuasa Córdova, 2015). Éstos parásitos que pertenecen a la clase de los cestodos, producen una zoonosis denominada dipilidiasis, transmitido por vía oral, al consumir accidentalmente a los hospederos intermediarios, como las pulgas de los perros, gatos y raramente de humanos por lo que representan un riesgo para las personas que utilizan los parques (Luzio et al, 2015;Vélez-Hernández et al, 2014).…”
Section: Discussionunclassified
“…En parques públicos del distrito de Santiago de Surco, Lima, Perú, se ha reportado una frecuencia de un 73,8% (18). En el municipio de Bucaramanga se reportó 40,54% (19) y en Bogotá 24,1% (20), siendo superiores a lo encontrado en el presente estudio. El resultado obtenido podría atribuirse a que las muestras de suelo del presente estudio proceden de zonas verdes cerradas, donde la afluencia de caninos y felinos es mucho menor que en parques públicos, donde se observa un alto número de caninos y felinos con y sin propietarios, lo que conlleva a una mayor contaminación fecal de estas zonas.…”
Section: Discussionunclassified